PENGARUH PENERAPAN MODEL MIND MAPPING TERHADAP HASIL BELAJAR TEMATIK SISWA SEKOLAH DASAR - Fernando, Elfis; Halidjah, Siti; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to analyze the effect of mind mapping models on the thematic learning outcomes of fifth grade students of South Pontianak 35 Primary School. The research method used is the experimental method. Quasi Experimental Design research form, with the type of Non Equivalent Control Group design. The population in this study were all fifth grade students, amounting to 96 students. The sample used was VC grade students totaling 32 students as a control class and VA totaling 31 students as an experimental class with random sampling techniques. Data collection techniques used are measurement techniques and data collection tools are written tests in the form of objective tests. The results of data analysis obtained an average of 72.91 posttest control results and the average posttest experimental results of 78.95. Based on the results of the t-test calculation, the  was 2,687 so that the  was 2,687>  1,671, then Ha was accepted. Effect Size calculation results obtained by 0.66, which is included in the criteria of being so that the application of mind mapping models give a moderate influence on the thematic learning outcomes of fifth grade students of South Pontianak 35 Primary School.Keywords: Influence, Learning Outcomes, Mind Mapping.